125 true stories of amazing animal friendships : inspiring true stories of unexpected friendships, purr-fect pals, and adorable best buds! - Gerry, Lisa (Washington, D.C. : National Geographic Kids, 2018)
"125 stories of unusual friendships between animals, for children"--
Introduction -- A friend in need -- Farmyard friends -- Odd couples -- Famous friends -- Babysitting buds -- Quirky cuties -- Fierce friends -- You've got a friend in me.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Ages 8-12.
Grades 4 to 6.
Description based on print version record.
Keywords: Animal behavior -- Anecdotes -- Juvenile literature; Social behavior in animals -- Anecdotes -- Juvenile literature; Animals -- Miscellanea -- Juvenile literature; Animals -- Habits and behavior -- Anecdotes; Social behavior in animals -- Anecdotes; Animals -- Miscellanea; JUVENILE NONFICTION -- Animals; JUVENILE NONFICTION -- Science & Nature -- Zoology; JUVENILE NONFICTION -- Social Topics -- Friendship; Animal behavior; Animals; Social behavior in animals; Electronic books- OSLIS; Trivia and miscellanea; Literature; Anecdotes; Juvenile works; Anecdotes; Literature; Trivia and miscellanea; Electronic books